Analyse de pratiques interdisciplinaires dans l’enseignement supérieur - Valérie Camel; Agnès Fargue-Lelièvre (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This study is a report covering several years on three teaching modules with different degrees of interdisciplinarity for engineering students. It examines issues regarding organisation and pedagogy and also advantages and limits both for students and teachers. These teaching modules are well appreciated by students, as they offer them an opportunity to establish links or interactions between disciplines usually dealt with separately, even though they may be somewhat disconcerted by this approach which differs from the monodisciplinary approach that they are familiar with. Self-learning is essential in order to encourage integration of disciplinary knowledge by the learners. As for the teachers, despite a higher investment requested for developing these interdisciplinary modules, they find a real interest, especially as far as opening up to other disciplines, that they can use in other teaching modules and in their research practice. Indeed, adopting an interdisciplinary approach offers a new perspective on one’s own discipline.